Spindlar: arm chair / Muhammad Hazim Ahmad Zawawi - Ahmad Zawawi, Muhammad Hazim (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Nature has always been a source of inspiration for humans. Human observed and tried to learn about natural forms and structures. Designers have also observed how life proceeded in nature and began to develop furniture by observing or imitating natural structures. Nature gave them plenty of opportunities with its admirable mechanisms, designs, and potential to enrich various aspects of life. To achieve the theme of nature-influenced furniture concept. There were five chosen of nature inspired, and the designer narrowed it down into three which are Maple Leaf, Periwinkle, and Spider. Research has been conducted to study the characteristics or details of nature and the designer selected Spider as the main inspiration. The design of the furniture focuses on the form and movement of spiders, especially on its leg. The target user for this design is an adult. After a few researches, the designer decided to choose the living room and bedroom as the main locations for the furniture. The aim of that survey was to understand the activities, lifestyle and problems that are involved with the existing furniture. As the result, the designer decided to design an arm chair that was inspired by spiders for the living room and bedroom. This arm chair has extra features such as a foot rest, phone, and cup holder. The design style is modern, and it looks different from the existing. The material used is using the combination of wood, plastic, and metal. The seat made from upholstery . The look of a crawling spider can be seen on the side panel design of the armchair.